Modern scientific approach to the treatment of gingivitis associated with biofilm in children and adolescents - Khomenko, Л. О.; Golubeva, І. М. (Actual Dentistry, 2024)
Summary. The article covers the modern scientifically based treatment concept of gingivitis, associated with biofilm, in childhood and adolescence. It is emphasized that the priority direction of combating microbial biofilm is regular individual and professional hygiene of the oral cavity. Mechanisms of action and age criteria for choosing antibacterial and antiinflammatory drugs for treatment of inflammatory periodontal diseases in children and adolescents are described. The need for supportive therapy to ensure periodontal health in children and adults is substantiated.